2018
DOI: 10.4172/neuropsychiatry.1000481
|View full text |Cite
|
Sign up to set email alerts
|

Is testosterone perspective available for neurodegenerative diseases?

Abstract: Neurodegenerative diseases such as Parkinson's disease and Alzheimer's disease are increasingly spreading worldwide. Neuroinflammation, deposition of misfolded proteins, oxidative stress, mitochondrial dysfunction, and excitotoxicity are main biological processes in the development of neurodegeneration. Furthermore, noncoding RNAs, genetic mutations, and environmental factors are involved in the development of neurodegeneration. Recent advances in the knowledge of testosterone shows that the concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
0
2
0
4
Order By: Relevance
“…AR has also played an important role in mediating androgens’ neuroprotective effects [ 69 , 71 ]. Hammond and colleagues demonstrated that serum deprivation-mediated neuronal apoptosis of human primary neurons was either eliminated entirely or significantly reduced at physiological concentrations of testosterone enanthate.…”
Section: Discussionmentioning
confidence: 99%
“…AR has also played an important role in mediating androgens’ neuroprotective effects [ 69 , 71 ]. Hammond and colleagues demonstrated that serum deprivation-mediated neuronal apoptosis of human primary neurons was either eliminated entirely or significantly reduced at physiological concentrations of testosterone enanthate.…”
Section: Discussionmentioning
confidence: 99%
“…Po przywróceniu terapii T, bądź DHT, odnotowano efekt ochronny [48]. Korzystne działanie androgenów obejmuje także opóźnianie apoptozy neuronów [61], wspieranie wzrostu neuronów [62] czy modulowanie uszkodzeń neuronalnych spowodowanych przez stres oksydacyjny przy jego niskim poziomie [63]. Należy tutaj zaznaczyć, że tkanka mózgowa jest znacznie bardziej wrażliwa na stres oksydacyjny niż inne tkanki.…”
Section: Rola Androgenów W Adunclassified
“…Dowody wskazują również na działanie neuroprotekcyjne i neuroregeneracyjne T po uszkodzeniach motoneurów [64]. Terapia zastępcza T przynosi rezultaty w poprawie pamięci werbalnej i przestrzennej, a także funkcjonowania poznawczego u mężczyzn z depresją w podeszłym wieku [62]. Pomimo licznych prac świadczących o pozytywnym wpływie T na funkcjonowanie poznawcze, m. in.…”
Section: Rola Androgenów W Adunclassified
“…The working memory is demarcated as a form of short-term memory that includes storage of information from a specific task and the information stored till it is useful to complete the task. Whereas the reference memory is demarcated as the long-term storage of information that is used from one task to another, testosterone seems to influence both these components of spatial memory, indicating its most consistent activational benefits [17, 18]. The testosterone can prevent neural tissue from entering into the apoptotic pathway [19].…”
Section: Introductionmentioning
confidence: 99%